Tax-Adjusted Duration for Amortizing Debt Instruments - Stock, Duane; Simonson, Donald G. (Journal of Financial and Quantitative Analysis, 1988)
This research provides improved techniques for analyzing the after-tax risk exposure of taxable institutions holding amortizing instruments such as commercial, real estate, and consumer loans. We derive after-tax duration for amortizing instruments and analyze it for sensitivity to tax rates, coupon, and maturity. Taxable investors who hedge and ignore the effects of taxes on amortizing instruments will underestimate differences in durations on bonds versus amortizing instruments of equal maturities; bond durations increase much faster as tax rates increase. One unexpected result shows that, unlike bond duration, amortizing instrument duration often increases with coupon rate, and sometimes is independent of coupon rate.